2016
DOI: 10.1002/pssb.201600519
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure calculation of Si1−xSnx compound alloy using interacting quasi‐band theory

Abstract: We investigate energy band structures of the Si1−xSnx compound alloy in the zincblende structure using interacting quasi‐band (IQB) theory. We first extend the IQB theory for four‐element compounds and subsequently calculate the electronic structures of the virtual Si1−xSnxSi1−ySny alloy where x = y. Diagonalizing a 20 × 20 non‐Hermitian Hamiltonian matrix using sp3s* empirical tight‐binding model with parameters obtained for the Si, Sn, and SiSn (zincblende) crystals, we obtain the electronic energy spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…the IQB theory, the absolute positions of the site energies are crucial. In our previous study on alloys, such as InGaN, [12][13][14] the N atom was common to both InN and GaN. In this scenario, the site energies ,…”
Section: ( )mentioning
confidence: 97%
See 2 more Smart Citations
“…the IQB theory, the absolute positions of the site energies are crucial. In our previous study on alloys, such as InGaN, [12][13][14] the N atom was common to both InN and GaN. In this scenario, the site energies ,…”
Section: ( )mentioning
confidence: 97%
“…11) This method is applicable to various alloys with diagonal and off-diagonal randomness, at any concentration. By extending the IQB theory and using the sp 3 s* (sp 3 ) empirical tight-binding model, we then calculated the electronic structures of typical III-V and II-VI semiconductor alloys with both the zincblende 12) and wurtzite structures 13) and successfully described the general behaviour of the concentration dependence of the top of the valence and the bottom of the conduction bands. When calculating the electronic structure of a cation-substituted alloy, for example III 1−x III′ x -V, the only necessaries are the sp 3 s* crystal parameters in the constituent III-V and III′-V semiconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the SiSn crystallization temperature can be reduced with a substitutional Sn content of around 30% [2]. In order to make SiSn alloys suitable for optical application, Masato Oda et al [9] utilized interacting quasi-band (IQB) theory and found that the indirect-direct gap crossover in Si 1−x Sn x occurs around x = 0.67 with Eg = 0.87 eV. There are also many studies on the optical and electrical properties and surface microstructure of SiSn films with an Sn concentration of 10-51% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Зокрема, кiлька теоретичних робiт передбачають, що перехiд непрямозонний-прямозонний напiвпровiдник у сплавах Si 1−x Sn x вiдбудеться за значень x вiд 0.25 до 0.67 залежно вiд методу розрахунку [2][3][4][5]. Ця вiдмiннiсть у результатах зумовлена, головно, труднощами врахування невпорядкованостi таких систем.…”
unclassified